Differences In The Results Of Examination Of Blood Glucose Levels By The Point Of Care Test (Poct) Method Using Vein And Capillary Blood Samples In Type II Diabetes Mellitus Patients - Artha Simamora; Karnirius Harefa (Institut Kesehatan Medistra Lubuk Pakam, 2023)
Glucose is an aldohexose monosaccharide found in the human body and other living things. It is the end product of carbohydrate metabolism that is released into the blood and becomes the main energy source of living things. Because of its role as the main energy, glucose is then transported into cells for generate energy. This energy formation process occurs in the mitochondria by requiring oxygen as fuel to produce ATP as energy for every cell activity. Blood glucose is influenced by factors of nutritional status, genetics and age, and disease. This study determine to differences in blood glucose levels measured using venous blood and capillary blood samples. This study used an analytical observational research design with a cross sectional approach. Observational research, which is to find differences between independent variables and dependent variables whose analysis is to determine whether there are differences between variables, so it is necessary to develop a hypothesis. Based on the results of the analysis of this study, it was found that from 25 respondents, the average value of capillary blood was 192.76, with a standard deviation of 56,302, with a min value of 111 and a max value of 288, with a p value of 0.007. The mean difference in venous blood is 186.44, with a standard deviation of 55.586, with a min value of 114 and a max of 280, with a p value = 0.007 with a significance level of p<? (0.05) which is 0.007<0.05. Based on the results of the study, it can be concluded that there are differences in the results of blood glucose levels using the POCT (Point Of Care Test) method using venous blood and capillary blood samples at Grandmed Lubuk Pakam Hospital